The Role of Innovative Behavior and Self-Efficacy as Mediators of The Influence of Competence And Work Discipline on The Performance of Vocational High School Teachers In Manokwari Regency - Rumbino, Naftalia; Mattalatta, Mattalatta; Echdar, Saban; Latief, Abdul (Devotion : Journal of Research and Community Service, 2024)
This study aims to examine  the role of innovative behavior and self-efficacy as a mediator of the influence of competence and work discipline on the performance of teachers of the State Vocational School of Manokwari Regency. This study uses a quantitative approach, with a sample of 189 respondents, data collection using questionnaires and using SEM-AMOS analysis. The test results showed: 1) competence and work discipline had a positive and significant effect on innovative behavior, 2) competence and work discipline had a positive and significant effect on self-efficacy, 3) competence had a positive and significant influence on teacher performance, while work discipline had no positive and significant effect on teacher performance, 4) innovative behavior and self-efficacy had a positive and significant effect on teacher performance,  5) Competence and work discipline have a positive and significant effect on teacher performance through innovative behavior, 6) Competence and work discipline have a positive and significant influence on teacher performance through self-efficacy. This study concludes that fostering innovative behavior and self-efficacy is essential to improving teacher performance, particularly in challenging educational settings.